2012
DOI: 10.1242/jeb.066910
|View full text |Cite
|
Sign up to set email alerts
|

Head and body stabilization in blowflies walking on differently structured substrates

Abstract: SUMMARYVisually guided animals depend heavily on the quality of visual signals in order to obtain functionally relevant information about their environment. To support visual information processing, nature has evolved a large variety of physiological adaptations and behavioral strategies such as compensatory head movements. During self-movement, head rotations compensate for changes in body attitude in order to stabilize gaze. However, how walking animals cope with uneven structured substrates, which may affec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
37
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 33 publications
(42 citation statements)
references
References 50 publications
4
37
1
Order By: Relevance
“…Although we have observed previously stride-coupled head yaw rotations of straight walking blowflies under visually impoverished and dark conditions (Kress and Egelhaaf, 2012), the finding that stride-coupled yaw gaze rotations were hardly compensated during visual fixation was unexpected. Roll and pitch components of body rotations are compensated by the head to a considerable extent, both in flying and in walking flies (Hengstenberg, 1991;Hengstenberg, 1993;Horn and Lang, 1978;Kress and Egelhaaf, 2012;Nalbach and Hengstenberg, 1993;Schwyn et al, 2011;van Hateren and Schilstra, 1999). A…”
Section: Potential Consequences Of Stride-coupled Gaze Shiftsmentioning
confidence: 52%
See 2 more Smart Citations
“…Although we have observed previously stride-coupled head yaw rotations of straight walking blowflies under visually impoverished and dark conditions (Kress and Egelhaaf, 2012), the finding that stride-coupled yaw gaze rotations were hardly compensated during visual fixation was unexpected. Roll and pitch components of body rotations are compensated by the head to a considerable extent, both in flying and in walking flies (Hengstenberg, 1991;Hengstenberg, 1993;Horn and Lang, 1978;Kress and Egelhaaf, 2012;Nalbach and Hengstenberg, 1993;Schwyn et al, 2011;van Hateren and Schilstra, 1999). A…”
Section: Potential Consequences Of Stride-coupled Gaze Shiftsmentioning
confidence: 52%
“…(C) Illustration of body (dark blue lines) and head (red lines) yaw orientation estimation. Yaw angles (Φ) were calculated from vector orientations based on the pixel coordinates of tracked marker points (see Kress and Egelhaaf, 2012 subdivided them into three classes, depending on whether the flies tended to fixate on the left edge, the center of the bar or the right edge. The classification was based on the criterion that the bar section with the lowest average retinal velocity was assumed to be the section that was fixated.…”
Section: Daniel Kress* and Martin Egelhaafmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the question as to whether these insects use gravity orientation cues to stabilize their attitude and hence their flight remains to be answered (Bender and Frye, 2009). In crickets and flies placed on tilted surfaces or a Styrofoam ball, gravity perception processes based on gravity-sensitive sensillae (Horn and Föller, 1998), leg load cues (Horn and Knapp, 1984;Hengstenberg, 1993;Kress and Egelhaaf, 2012;Mendes et al, 2014) and antennal receptors (Horn and Kessler, 1975;Horn and Bischof, 1983;Kamikouchi et al, 2009) enable insects to stabilize their gaze and compensate for their body tilt, but it has not yet been established whether they use gravity perception processes during flight. In the cockroach, the tricholiths -pendulous gravity-sensitive sensilla located on the cerci (Walthall and Hartman, 1981;Hartman et al, 1987) -were reported to be involved in contralateral wingbeating and possibly in flight equilibrium (Fraser, 1977).…”
Section: Introductionmentioning
confidence: 99%
“…In our study, head and body movements of the seals were analysed as a first approximation for gaze movements (see Eckmeier et al, 2008;Kress and Egelhaaf, 2012;Kress and Egelhaaf, 2014b) because eye movements could not be resolved in our video recordings. Seals have mobile eyes Hanke et al, 2008), so saccadic eye movements might add to the saccadic head and body shifts, as was reported for goldfish (Easter et al, 1974) and cichlid fish (Fernald, 1975(Fernald, , 1985.…”
Section: Discussionmentioning
confidence: 99%